2009
DOI: 10.2135/cropsci2008.09.0566
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability in Nitrogen Use Efficiency of Spring Barley

Abstract: Increasing costs of N fertilizers and the negative impact of excessive N on the environment have made improvement in nitrogen use efficiency (NUE) a desirable goal in barley (Hordeum vulgare L.) breeding. Seventeen replicated trials, each consisting of 15 to 20 genotypes, were performed across different environments in Alberta, Canada from 1998 to 2007 to determine genetic variability in NUE. Further, 25 genotypes were grown at six environments in 2007 for analysis of the pattern of genotypic variation for NUE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 27 publications
6
69
0
Order By: Relevance
“…Dawson et al (2008) suggested that under these conditions, plants are unable to assimilate enough N and losses rise resulting in low NUE. In our study, highest NUE and grain yield was recorded for genotypes GLU 1356 and GLU 2001 under sub-optimal doses of N. Field studies on barley have clearly shown differences in the NUE of various genotypes (Abeledo et al, 2008;Anbessa et al, 2009), which can be improved by increasing N uptake and NUE under low N supply (Moose and Below, 2009;Beatty et al, 2010). Very low NUE of even 6% was registered for wheat genotypes under 180 kg N ha -1 of urea ammonium nitrate which could be attributed to N loss to environment (Kanampiu et al, 1997).…”
Section: Discussionsupporting
confidence: 48%
“…Dawson et al (2008) suggested that under these conditions, plants are unable to assimilate enough N and losses rise resulting in low NUE. In our study, highest NUE and grain yield was recorded for genotypes GLU 1356 and GLU 2001 under sub-optimal doses of N. Field studies on barley have clearly shown differences in the NUE of various genotypes (Abeledo et al, 2008;Anbessa et al, 2009), which can be improved by increasing N uptake and NUE under low N supply (Moose and Below, 2009;Beatty et al, 2010). Very low NUE of even 6% was registered for wheat genotypes under 180 kg N ha -1 of urea ammonium nitrate which could be attributed to N loss to environment (Kanampiu et al, 1997).…”
Section: Discussionsupporting
confidence: 48%
“…The approach is here exemplified for winter wheat grown in Central Sweden (Table 1) and has recently been used by many authors (e.g. Anbessa et al 2009;Foulkes et al 2009;Sylvester-Bradley and Kindred 2009). The concept of Moll et al (1982) certainly is meaningful in an applied agronomic perspective with focus only on cereals, but has serious limitations especially when the NUE of different crops and production systems should be compared.…”
Section: Cereal Growth and Nitrogen Use Efficiencymentioning
confidence: 99%
“…These include root length density and improve post-anthesis (after flower pollination/fertilization) re-translocation of N from straw. Anbessa et al (2009) suggest that NUE is significantly affected by both genotype and environment. Recent unpublished research (Ian Bingham, pers.…”
Section: Species Introductionmentioning
confidence: 97%